استدراكات الشيخ عبدالرحمان السعدي على مذهب الحنابلة - فتح الله محمد; الياس بلقاسمي; بوفاتح الطيب (جامعة عمار ثليجي الاغواط, 2024)
ملخص: المذكرة مقدمة مذكرة في رحاب الشريعة الإسلامية، تحتل الزكاة مكانة مرموقة بوصفها أحد أركان الإسلام الخمسة. ومن هذا المنطلق، تأتي دراسة استدراكات الشيخ عبد الرحمن السعدي على فقهاء الحنابلة في كتاب الزكاة لتسلط الضوء على أحد أعلام الفقه الحنبلي المعاصر، وتكشف عن إسهاماته القيّمة في تجديد الفقه الإسلامي وتطويره. منهجية البحث تعتمد هذه الدراسة على منهجية علمية متكاملة تشمل: المنهج الاستقرائي: لجمع وتتبع استدراكات الشيخ السعدي من مصادرها الأصلية بدقة وأمانة. المنهج التحليلي: لتحليل هذه الاستدراكات ومقارنتها بأقوال فقهاء الحنابلة بغية فهم الفروق والتمايزات. المنهج المقارن : لتقييم هذه الاستدراكات ونقدها بموضوعية، بهدف الوقوف على مدى دقتها وملاءمتها للواقع المعاصر. نبذة عن الشيخ عبد الرحمن السعدي ومؤلفاته تقدم المذكرة في فصلها الأول لمحة عن حياة الشيخ عبد الرحمن السعدي، مسيرته التعليمية، شيوخه ومؤلفاته، مع التركيز على دوره الرائد في مجال الفقه الحنبلي، وتأثيره الكبير في تطوير الأحكام الفقهية المتعلقة بالزكاة. مفهوم الاستدراك في الفقه تستعرض المذكرة في بداية الفصل الثاني مفهوم الاستدراك في الفقه الإسلامي، وتبرز أهميته كأداة لتطوير الفقه وتصحيح مسائله. كما تقدم أمثلة عن استدراكات علماء الفقه، مشيرة إلى دورها في إثراء التراث الفقهي الإسلامي. استدراكات الشيخ السعدي على فقهاء الحنابلة في كتاب الزكاة في هذا الجزء المحوري، تتناول المذكرة استدراكات الشيخ السعدي على فقهاء الحنابلة في مسائل الزكاة المختلفة: مسائل عامة في أحكام الزكاة تُقدم في هذا القسم تعريف الزكاة وشروط وجوبها، موضحًا الأساسيات اللازمة لفهم هذا الركن العظيم من أركان الإسلام. مسائل أخرى متنوعة يستعرض هذا القسم استدراكات الشيخ السعدي على مسائل متفرقة في فقه الزكاة، مثل زكاة النقدين، زكاة عروض التجارة، وزكاة الزروع والثمار. يتم تحليل وتفصيل آرائه مقارنةً بآراء فقهاء الحنابلة. أمثلة تطبيقية على استدراكات السعدي يُقدِّم هذا القسم أمثلة تطبيقية لبعض استدراكات الشيخ السعدي، مشفوعة بشرح تفصيلي لكل منها. يتم أيضًا مقارنة هذه الأمثلة بآراء فقهاء الحنابلة، مع بيان الأسباب التي دفعت الشيخ السعدي إلى هذه الاستدراكات، مما يعزز فهمنا للتحولات الفقهية التي قدَّمها. تقييم وتحليل استدراكات السعدي يتناول هذا القسم تحليلًا معمقًا لاستدراكات الشيخ السعدي، مع التركيز على دقتها وتأثيرها على الفقه الحنبلي. يتم تقييم مدى قبولها واستحسانها من قبل العلماء والباحثين في الفقه الإسلامي، مما يساهم في تقديم رؤية شاملة لتأثير هذه الاستدراكات على الفقه الإسلامي المعاصر. خاتمة واستنتاجات تختتم المذكرة بأهم النتائج التي توصلت إليها الدراسة، مسلطة الضوء على أثر استدراكات الشيخ السعدي في تصحيح بعض المسائل الفقهية المتعلقة بالزكاة، وتقديم رؤية جديدة لبعض القضايا الفقهية. التوصيات تقدم المذكرة توصيات مهمة لمزيد من الدراسات في مجال استدراكات الفقهاء، مشددة على أهمية مراجعة الأحكام الفقهية باستمرار لضمان دقتها وملاءمتها لمتغيرات العصر. المراجع والمصادر تختتم المذكرة بذكر قائمة المراجع والمصادر التي اعتمدت عليها الدراسة، والتي تشمل كتب الفقه الحنبلي، ومؤلفات الشيخ السعدي، والدراسات الحديثة في مجال الفقه الإسلامي. تعد هذه المذكرة إضافة ثمينة للمكتبة الفقهية الإسلامية، إذ تبرز دور العلماء المعاصرين في تجديد الفقه وتصحيح مسائله، مما يثري الفكر الإسلامي ويدعمه بالتوجهات الفقهية المعاصرة. Abstract In the realm of Islamic law, zakat holds a prominent position as one of the five pillars of Islam. This study of Sheikh Abdul Rahman Al-Sa’di’s critiques of Hanbali jurists in the book of zakat aims to shed light on one of the eminent contemporary Hanbali scholars and reveal his valuable contributions to the renewal and development of Islamic jurisprudence. Research Methodology This study relies on an integrated scientific methodology, including: The Inductive Method: To accurately and faithfully collect and trace Sheikh Al-Sa’di’s critiques from their original sources. The Analytical Method: To analyze these critiques and compare them with the opinions of Hanbali jurists to understand the differences and distinctions. The Critical Method: To objectively evaluate these critiques to determine their accuracy and relevance to the contemporary context. Overview of Sheikh Abdul Rahman Al-Sa’di and His Works The first chapter of thesis provides an overview of the life of Sheikh Abdul Rahman Al-Sa’di, his educational journey, his teachers, and his works, with a focus on his pioneering role in Hanbali jurisprudence and his significant influence on the development of legal rulings related to zakat. Concept of Critique in Islamic Jurisprudence At the beginning of the second chapter,thesis explores the concept of critique in Islamic jurisprudence, highlighting its importance as a tool for the development and correction of legal issues. Examples of critiques by jurists are presented, demonstrating their role in enriching the Islamic legal heritage. Critiques of Sheikh Al-Sa’di on Hanbali Jurists in the Book of Zakat General Issues in the Rules of Zakat This section presents the definition of zakat and the conditions for its obligation, explaining the basics necessary to understand this essential pillar of Islam. Various Other Issues This section examines Sheikh Al-Sa’di’s critiques on various issues in zakat jurisprudence, such as zakat on gold and silver, zakat on trade goods, and zakat on crops and fruits. Al-Sa’di’s opinions are analyzed and detailed in comparison with the views of Hanbali jurists. Practical Examples of Al-Sa’di’s Critiques This section provides practical examples of some of Sheikh Al-Sa’di’s critiques, accompanied by a detailed explanation of each. These examples are also compared with the views of Hanbali jurists, explaining the reasons that led Sheikh Al-Sa’di to these critiques, thereby enhancing our understanding of the jurisprudential developments he proposed. Evaluation and Analysis of Al-Sa’di’s Critiques This section offers an in-depth analysis of Sheikh Al-Sa’di’s critiques, focusing on their accuracy and impact on Hanbali jurisprudence. The acceptance and appreciation of these critiques by scholars and researchers in Islamic jurisprudence are assessed, contributing to a comprehensive view of the influence of these critiques on contemporary Islamic jurisprudence. Conclusion and Findings The thesis concludes with the main findings of the study, highlighting the impact of Sheikh Al-Sa’di’s critiques in correcting some legal issues related to zakat and offering a new perspective on certain jurisprudential issues. Recommendations The thesis provides important recommendations for further studies in the field of juristic critiques, emphasizing the importance of continuously reviewing legal rulings to ensure their accuracy and relevance to contemporary changes. References and Sources The thesis concludes with a list of references and sources used in the study, including books on Hanbali jurisprudence, the works of Sheikh Al-Sa’di, and modern studies in the field of Islamic jurisprudence. This thesis constitutes a valuable contribution to the Islamic legal library, highlighting the role of contemporary scholars in renewing and correcting legal issues, thereby enriching Islamic thought with contemporary juristic orientations.
باب الزكاة انموذجا